2019
DOI: 10.1177/1687814018819563
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution of the train brake disc during high-speed braking

Abstract: Temperature evolution of the train brake disc during high-speed braking was investigated using in situ experiments, theoretical analysis, and finite element modeling. The experimental results show that the temperature distribution on the friction surface experienced the formation of a hot ring first, then expansion and duration of the hot ring. Alternative hot spot and cold zone were observed on the friction surface, which is attributed to the local contact in the friction couple and heterogeneous heat dissipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
(36 reference statements)
1
16
0
5
Order By: Relevance
“…This is not surprising, as these points are 'far' from heat source area. In accordance with the presented results, other studies also confirmed maximum temperature location at mid-surface of disc [24,34]. On the other hand, this finding is contrary to previous studies who reported maximum temperature at outer radius of disc [23]; meanwhile, others reported extreme radius (inner and outer) as location of maximum temperature [22,35].…”
Section: Friction Heating Boundary Value Problemsupporting
confidence: 88%
“…This is not surprising, as these points are 'far' from heat source area. In accordance with the presented results, other studies also confirmed maximum temperature location at mid-surface of disc [24,34]. On the other hand, this finding is contrary to previous studies who reported maximum temperature at outer radius of disc [23]; meanwhile, others reported extreme radius (inner and outer) as location of maximum temperature [22,35].…”
Section: Friction Heating Boundary Value Problemsupporting
confidence: 88%
“…Wang et al studied the temperature trends of train brake discs in the process of high-speed braking and concluded that the change in temperature causes fluctuation in the instantaneous friction coefficient and a distribution of thermal stress on the brake disc, which implied thermal damage [12] . B. Ghadimi et al conducted a three-dimensional simulation analysis on the brake temperature field of the wheel-mounted brake disc of an ER24PC locomotive and compared the results with experimental results.…”
Section: School Of Mechanical Electronic and Control Engineeringmentioning
confidence: 99%
“…The temperature evolution of the train brake disc during high-speed braking was investigated using the infrared thermography technique, as well as the finite element modeling in the paper [ 23 ]. Moreover, the one-dimensional heat conduction model was applied to calculate the maximum temperature variations during single braking, based on the solution received in the paper [ 24 ].…”
Section: Introductionmentioning
confidence: 99%